Systemic analysis of a drug trafficking mess. (3rd October 2019) - Sapiano, Nicholas J.; Hester, Patrick T.
In an effort to combat drug trafficking at the federal level, the USA faces an unenviable task. Trying to address this situation involves consideration of drug production, importation and consumption. The think-act-observe (TAO) approach of Hester and Adams (2017) provides a systems theory-based multi-methodology for addressing these and other complex, interconnected problems. After an articulation of the constituent problems of the mess and their collective stakeholders, the problems are individually subjected to systemic analysis in the think stage; further, the production problem analysis is reported in detail as a case study. These problem-level analyses are then integrated and utilised in the act stage to analyse the systemic impact of potential mess interventions. Recommendations for future action are provided in support of the observation stage. Problem owners can then move forward in an effort to resolve the mess in a manner satisfactory to all affected parties.